PENGARUH PERBANKAN SYARIAH TERHADAP HUKUM PERBANKAN NASIONAL - Imaniyati, Neni Sri (LPPM Unisba, 2011)
Syariah Bank, which has been existence in Indonesia for two decades, is undergoing a fast development. According to Islamic Finance Reportâs survey that Syariah Banking in Indonesia is in the fourth rank under Malaysia,Iran, dan Arab Saudi. The Banking system offers, both conventional banking, and non-bank finance company services. The establishment of Syariah Bank is much influenced by Islamic law system. The aim of this article is to give an overview of how banking concept in Islam and aspects in national banking law influenced by Syariah Banking. It is concluded from this research that Banking in Islam is an economic activity based on the Syariah Economic Principles, namely the Principles ofÂ Tauhid, Khilafah, andÂ Adalah. The influence ofÂ Syariah Banking on national banking lawÂ can be seen in the use ofÂ Â contract based on Syariah Principles.